The visible spectroscopy of iron oxide minerals in dust particles from ice cores on the Tibetan Plateau - Wu, Guangjian; Xu, Tianli; Zhang, Xuelei; Zhang, Chenglong; Yan, Ni (Tellus B: Chemical and Physical Meteorology, 2016)
Goethite (Gt) and hematite (Hm) are the most abundant forms of iron oxides in dust and the major light absorbers in the shortwave spectrum in air and snow. Diffuse reflectance spectrometry was performed to investigate the reflectance spectra of goethite and hematite in dust particles from ice cores, aerosol samples and glacier cryoconite on the northern and central Tibetan Plateau. The results showed that two peaks in the first derivative value of the spectra at 430 and 560 nm were determined to be goethite and hematite, respectively. The high iron content samples have a higher first derivative value, and prominent and much more distinct peaks for Hm and Gt. We propose that the strength of the Hm and Gt peaks may probe the iron content, and then in our samples hematite has a stronger correlation than goethite. However, when the iron content reaches a threshold, the iron oxides have little or no impact on the reflectance spectra. The fine fraction of glacier dust has a greater abundance of iron, and the first derivative values of hematite are higher than goethite, indicating that hematite might be concentrated in the fine fraction. The distinguishable differences in the Hm/Gt ratio among these ice core samples and other aerosol data indicate the regional to continental difference in composition, which can be used to simplify the iron oxides in snow radiation models.